Police Databases and Crime Information Management - Sangtongdee, Usanut (Journal of Innovation and Management, 2020)
This academic article aims to present the concept of the development of police information systems. Royal Thai Police is responsible for controlling crimes committed in Thailand. Police stations are the default units initiating a data belt of crime. Information management systems by police apply for criminal investigation, crime prevention and suppression. For reported incidents, if they are either the criminal case or traffic accident, an interrogation unit must initialize the process. Designing collection and sharing litigation information in a system involves providing both same operation-level and policy-level agencies. The exchange of data insight is vital to the police force in the digital era. POLIS is an information system which was the critical service in the early days. CRIMES is a continued development came later. The separation of criminal databases from the administrative parts is a significant turning point in the latter stages’ growth. However, organizational data related to human resources and budget is also required to maintain cross-system links. The future approach to police station systems focuses on hardware and software optimization. Moreover, the adoption of artificial intelligence technology to support crime analysis and investigations as consideration.